SNPs from BCHE and DRD3 genes associated to cocaine abuse amongst violent individuals from Sao Paulo, Brazil. (December 2020) - Pego, A.M.F.; Leyton, V.; Miziara, I.D.; Bortolin, R.H.; Freitas, R.C.C.; Hirata, M.; Tomaz, P.R.X.; Santos, J.R.; Santos, P.C.J.L.; Yonamine, M.
Graphical abstract: Highlights: Chronic and recent cocaine use seen in 53 and 51% of the individuals, respectively. The use of cocaine may be highly linked with risky/violent behaviours. SNPs rs4263329 and rs6280 yielded significant differences among cases and controls. A potential preliminary association between genetics and cocaine abuse is suggested. Attempts contributing to prevention of drug abuse are highly necessary. Abstract: Violence and drug abuse are highly destructive phenomena found world-wide, especially in Brazil. They seem to rise proportionally to one another and possibly related. Additionally, genetics may also play a role in drug abuse. This study has focused on identifying the use of cocaine within postmortem cases arriving at the Institute of Legal Medicine of Sao Paulo as well as the presence of certain single nucleotide polymorphisms (SNPs) to better understand one's susceptibility to abuse the drug. Both hair and blood samples have been extracted through a simple methanol overnight incubation or a rapid dilute-and-shoot method, respectively. The samples were then analyzed using an UPLC-ESI-MS/MS and genotyped through RT-PCR. Statistical analyses were performed via SPSS software. From 105 postmortem cases, 53% and 51% of the cases shown to be positive for cocaine in hair and blood, respectively. Genetic wise, a significant difference has been observed for SNP rs4263329 from the BCHE gene with higher frequencies of the genotypes A/G and G/G seen in cocaine users (OR = 8.91; 95%CI = 1.58–50.21; p = 0.01). Likewise, also SNP rs6280 from the DRD3 gene presented a significant association, with both genotypes T/C and C/C being more frequent in users (OR = 4.96; 95% CI = 1.07–23.02; p = 0.04). To conclude, a rather high proportion of cocaine has been found, which may suggest a connotation between the use of the drug and risky/violent behaviors. Additionally, significant associations were also found within two SNPs related to cocaine use, however, due to several inherent limitations, these must be confirmed.